Mobile soil bin development and testing - Zeller, Jonathan (Kansas State University, 2018)
In 2050 the world’s population is projected to be over 9 billion people, creating a need for more agriculture production than ever before. One way to increase production of crops is to get them planted in an optimum planting window. This allows the crops to take the most advantage of the longer days during the growing season thus increasing their yield. The growing size of farms and reduced amount of farmers puts more pressure on each remaining farmer to mechanize more heavily, and to get more acres planted faster in order to get crops planted in time. Most areas have an optimal planting window of a few weeks. This drives a need for planters to get bigger so one man can plant more acres in a day. Besides getting bigger, planters are also getting able to accurately plant faster. Today many of the new planters are “high speed,” meaning they are able to plant at speeds of 7 to 10 mph. The typical research and discussions of high speed planters tend to focus on the speed effects on the seed placement, emergence, planting rates, active downforce systems, metering systems etc. There is little discussion on the effects these higher planting speeds have on the draft requirements of the row unit itself. There needs to be more knowledge about the relationship between soil and planting tools in order to optimize power and performance of the tools to minimize fuel consumption, labor, and soil compaction. In order to test the draft forces of various tillage and planting tools in different field conditions there needs to be a machine that can repeatedly test multiple tools in multiple field conditions over a wide range of speeds. This paper is about the development of such a machine. The Cultivation Assessment Test Apparatus (CAT App.) is a device used to pull tillage and planting tools at a consistent depth at different speeds measuring the draft and downforce requirements during tests.
Keywords: Design; Tillage; Planting; Downforce; Draft